2002
DOI: 10.1111/j.1550-7408.2002.tb00350.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Expressed Sequence Tags (ESTs) in the Ciliated Protozoan Tetrahymena thermophila

Abstract: To assess the utility of expressed sequence tag (EST) sequencing as a method of gene discovery in the ciliated protozoan Tetrahymena thermophila, we have sequenced either the 5' or 3' ends of 157 clones chosen at random from two cDNA libraries constructed from the mRNA of vegetatively growing cultures. Of 116 total non-redundant clones, 8.6% represented genes previously cloned in Tetrahymena. Fifty-two percent had significant identity to genes from other organisms represented in GenBank, of which 92% matched h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 63 publications
0
22
0
6
Order By: Relevance
“…It will be of interest to determine whether REP elements are capable of transposition during vegetative growth. We have previously identified a growth-associated piwi-related gene in an expressed sequence tag sequencing project (20). Caenorhabditis elegans mutants carrying mutations in the piwirelated gene rde-1 exhibit transposon mobilization (51).…”
Section: Discussionmentioning
confidence: 99%
“…It will be of interest to determine whether REP elements are capable of transposition during vegetative growth. We have previously identified a growth-associated piwi-related gene in an expressed sequence tag sequencing project (20). Caenorhabditis elegans mutants carrying mutations in the piwirelated gene rde-1 exhibit transposon mobilization (51).…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal sequence of the purified protein (Pgp1p) exactly matched residues 22 to 40 of a predicted protein encoded by a cDNA from a Tetrahymena expressed sequence tag cDNA library (12). The full-length sequence of PGP1 was obtained by 5Šˆ and 3Šˆ rapid amplification of cDNA ends (36).…”
Section: Methodsmentioning
confidence: 99%
“…To date, research using T. thermophila has made great contributions to fundamental biological discoveries such as dynein [8], catalytic RNA [9], telomeric repeats [10,11], telomerase [12], the function of histone acetylation [13], and RNAi mechanisms in macronucleus reprogramming [14]. Analysis of expressed sequence tags in the genome of Tetrahymena has demonstrated that it has a high degree of functional homology with human and mammalian genomes [15]. The organism also shares many core processes with a wide variety of eukaryotes (including humans) [16] that are not found in other single-celled model systems (e.g., yeast).…”
mentioning
confidence: 99%